El complejo del rapé: Un diseño de investigación. - Benavente, Antonia; Massone, Claudio; Thomas, Carlos (Revista Chilena de Humanidades, 2016)
The present work proposes a design of investigation concerning the rapé complex in Chile, characteristic of the so-called culture of San Pedro . With this aim in view, nearly a thousand contexts proceeding from different cemeteries in the oasis of San Pedro of Atacama are examined. In this way, the main lines as well as the sets of problems deriving from this information a rebrought to our notice.